2020
DOI: 10.2217/fvl-2020-0170
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of lactoferrin, Ovotransferrin and Lysozyme As Antiviral and immune-modulating Agents in COVID-19

Abstract: Coronavirus disease 2019 (COVID-19), caused by SARS coronavirus 2 (SARS-CoV-2), is spreading rapidly with no established effective treatments. While most cases are mild, others experience uncontrolled inflammatory responses with oxidative stress, dysregulation of iron and coagulation as features. Lactoferrin, ovotransferrin and lysozyme are abundant, safe antimicrobials that have wide antiviral as well as immunomodulatory properties. In particular, lactoferrin restores iron homeostasis and inhibits replication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 172 publications
(213 reference statements)
0
36
0
4
Order By: Relevance
“…Lactoferrin is a component of many commercial products, including that of babies’ milk formula. As seen in other in vitro studies, lactoferrin, which is expressed in most biological fluids, has been shown to inhibit a variety of pathogens including influenza A and a virus closely related to SARS-CoV-2, the Severe Acute Respiratory virus (SARS-CoV) from 2003 [ 16 ]. In this paper, we have demonstrated that lactoferrin is also capable of inhibiting SARS-CoV-2 when used as an antiviral application on fabric material.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lactoferrin is a component of many commercial products, including that of babies’ milk formula. As seen in other in vitro studies, lactoferrin, which is expressed in most biological fluids, has been shown to inhibit a variety of pathogens including influenza A and a virus closely related to SARS-CoV-2, the Severe Acute Respiratory virus (SARS-CoV) from 2003 [ 16 ]. In this paper, we have demonstrated that lactoferrin is also capable of inhibiting SARS-CoV-2 when used as an antiviral application on fabric material.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we have demonstrated that lactoferrin is also capable of inhibiting SARS-CoV-2 when used as an antiviral application on fabric material. While the exact mechanism for inhibition of SARS-CoV-2 by lactoferrin is unknown, it has been shown to inhibit viral entry for related-virus SARS-CoV either through virus-binding or cell surface molecule binding [ 16 , 17 , 18 , 19 ]. In clinical trials where lactoferrin is used as an antiviral, it has been shown to reduce the severity and duration of disease in patients with SARS-CoV-2 within 4–5 days after oral administration and prevent contraction of SARS-CoV-2 in 256 people (100% of participants) with contact with these infected symptomatic individuals [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism may be that the hydrophobic amino acid of lysozyme, especially residue 5-39, reacted with structural protein of MNV-1 after exposure to thermal denatured, resulting in inactivity of MNV-1, thereby exerting the antiviral effect. In addition, Kelly Mann et al [26] found that lysozyme could significantly inhibit the production of proinflammatory cytokines such as TNF-α and IL-6, block the formation of AGEs, and enhance the excretion capacity of kidney. Moreover, when simulated gastrointestinal digestion, hen egg white lysozyme could exhibit significant antioxidant activity and angiotensin converting enzyme (ACE) inhibitory activity, so lysozyme had the potential as an antiviral and immunomodulatory drugs in the treatment of COVID-19.…”
Section: Application In the Treatment Of Viral Diseasesmentioning
confidence: 99%
“…With a strong and selective affinity with iron ions, these drugs can bind free iron and remove it from iron-storing proteins [ 10 , 11 ]. Recent studies have demonstrated that some natural components of the human innate immunity could act as a first barrier against viral injury and, in this regard, increasing interest has been shown in the possible preventive role of lactoferrin as adjunct treatment [ 12 , 13 ]. Lactoferrin is a glycoprotein of human secretion, belonging to a non-specific defensive system, known to play a pivotal role against viral infections and able to regulate iron metabolism.…”
Section: Introductionmentioning
confidence: 99%